“Building that World”: Movements of Vision in the Carceral Classroom - Cates, Rhiannon M.; Hall, Benjamin J.; Broughton, James; Reeves, Andrew; Hocutt Ringwelski, Faith; Zaro, Kathryn; Richards, Jenna; Roberts, Lani (Radical Teacher, 2020)
An article in which two teaching assistants and six students of a university course taught inside a correctional facility, "Writing as Activism," collaboratively examine their experience as co-teachers and co-learners in a humanities-based prison classroom. Fostered and framed by their instructor’s critical and transformative pedagogical approaches in this course, the authors locate integrated learning and collaborative writing within carceral classrooms as sites for intentional and resistant futures to be enacted and embodied as a practice of post-carceral world-building. The students enter their individual narratives into this location of their experience of envisioning and enacting resistant futures together in this space as a student movement dedicated and equipped to bring a world beyond prison into being.